Fault diagnosis method for driving part of position control solenoid valve - Lee, Jun Seong; Hong, Seung Geon; Park, John Oh; Chai, Jang Bom; Park, Il Han (Transactions of the Korean Institute of Electrical Engineers, 2020)
The position control solenoid operated valve(SOV), which is mainly used in the exhaust system of nuclear power plants, uses a position sensor for more precise control than a generally used solenoid valve. The position of the valve plunger is transferred to the control unit, and the duty ratio of the voltage applied to the coil is adjusted through the PWM. Thus, the current of the operating SOV varies depending on the plunger position and the duty ratio. In this paper, we propose a method for diagnosing fault of the driving part of a SOV using an equivalent electric circuit. The operating current of SOV are compared with the reference current from the equivalent circuit to diagnose the fault. To take into account the dependence of the operating on the plunger position and duty ratio, the circuit parameters are calculated by repeating numerical analysis, and the resulted values are interpolated to make them a function. To verify the validity of the proposed fault diagnosis method, the major faults of SOV are implemented in a numerical analysis model and compared with the current of an equivalent circuit.
Keywords: Circuit parameter; Equivalent electric circuits; Fault diagnosis method; Numerical analysis models; Operating currents; Position sensors; Precise control; Reference currents; Equivalent electric circuit; Fault diagnosis; Numerical analysis; Solenoid valve